Association of low income with pulmonary disease progression in smokers with and without chronic obstructive pulmonary disease. Issue 4 (12th November 2018) - Lowe, Katherine E.; Make, Barry J.; Crapo, James D.; Kinney, Gregory L.; Hokanson, John E.; Kim, Victor; Iyer, Anand S.; Bhatt, Surya P.; Hoth, Karin F.; Holm, Kristen E.; Wise, Robert; DeMeo, Dawn; et al.
Low socioeconomic status has been associated with chronic obstructive pulmonary disease (COPD) but little is known about its impact on disease progression. We assessed the association of income to symptoms, pulmonary disease severity and progression in smokers with and without COPD. The COPDGene cohort of 4826 smokers who reported annual income in phase 2 was analysed. Those who reported annual income <USD 15 000 per year were "low-income" and the remainder "higher income". Baseline demographics, symptoms, computed tomography (CT) imaging, and 5-year change in spirometry and CT metrics were characterised by group. The low income group was younger (55.7 versus 61.7, p<0.0001), had more current smokers (73% versus 36%, p<0.0001), higher rates of severe exacerbations (13% versus 7%, p<0.0001), more chronic bronchitis (22% versus 14%, p<0.0001), reduced access to preventative care and lower quality of life, but less emphysema (4.7% versus 6.2%, p<0.0001). After 5 years the low-income group had more smoking-related disease progression, without significant change in exacerbations or symptoms, than higher-income subjects. Low income was an independent predictor of decreasing forced expiratory volume in 1 s (FEV1 ) (p=0.001) and increased airway disease (p=0.007) after adjusting for baseline FEV1, age, sex, race, exposures and current smoking. Income disparity beyond the effects of race and current smoking is an important factor for disease progression. Worldwide, poverty and its consequences: associated respiratory exposures, limited healthcare access, and inadequate education about smoking risks, may exacerbate chronic lung disease. Income is a factor in predicting pulmonary disease progression in smokers with and without COPD; those with lower income experience faster progression and worse symptoms http://ow.ly/1SSe30lU1cX